Assessing the potential of fuel cell-powered and battery-powered forklifts for reducing GHG emissions using clean surplus power; a game theory approach. (4th December 2020) - Haghi, Ehsan; Shamsi, Hamidreza; Dimitrov, Stanko; Fowler, Michael; Raahemifar, Kaamran
Abstract: This work aims at developing a game theory model for assessing the potential of fuel cell-powered and battery-powered forklifts for reducing GHG emissions in the province of Ontario, Canada. Two stakeholders are considered in the developed model: government and energy consumer. The energy consumer, which is assumed to be an industrial facility, operates 150 diesel forklifts but has the option of replacing them with fuel cell-powered and battery-powered forklifts. The government can encourage this replacement by allocating a percentage of Ontario's surplus power to the energy consumer at a discounted price. The discount is assumed to be exempting the energy consumer from paying the global adjustment. As a result, the energy consumer only pays the hourly Ontario electricity price when discounted power is available. Discounted electricity will decrease the cost of operating battery-powered and fuel cell-powered forklifts for the energy consumer and will encourage it to use those technologies instead of diesel forklifts. The government has an incentive to pursue such policy as the replacement of diesel forklifts with fuel cell-powered and battery-powered forklifts will reduce GHG emissions and subsequently, the social cost of carbon in the province. The reults of our modeling show that when the government does not allocate discounted power to the energy consumer, energy consumer does not reduce emissions and keeps using its 150 diesel forklifts. However, when the government provides 0.1% of Ontario's surplus power at each hour to the energy consumer at a discounted price, the energy consumer replaces 31 of its diesel forklifts with battery-powered forklifts. When the percentage of discounted power is 0.6% of Ontario's surplus power at each hour, energy consumer replaces 91 of its diesel forklifts with battery-powered forklifts and 54 of its diesel forklifts with fuel cellpowered forklifts. A policy of discounting surplus power to encourage replacing diesel forklifts with battery-powered and fuel cell-powered forklifts is shown to benefit both stakeholders in the system. Our analysis also shows that the deployment of both fuel-cell powered and battery-powered forklifts is effective in reducing GHG emissions in Ontario when surplus clean power is available. Battery-powered forklifts are more cost-effective when lower levels of discounted power are available; however, with an increase in the level of available discounted power, fuel cell-powered forklifts become more cost-effective technologies compared to battery-powered forklifts. Highlights: Assessment of the potential of battery-powered forklifts in emission reduction. Assessment of the potential of fuel cell-powered forklifts in emission reduction. Game theory is used for modeling the interaction of the stakeholders. Battery and hydrogen technologies are complementary in reducing GHG emissions. Both government and energy consumer benefit from incentivizing clean technologies.